Lesbian, Gay, Bisexual, and Transgender Youth and Family Acceptance - Katz-Wise, Sabra L; Rosario, Margaret; Tsappis, Michael (The Pediatric clinics of North America, 2016)
In this article, we address theories of attachment and parental acceptance and rejection, and their implications for lesbian, gay, bisexual, and transgender (LGBT) youths' identity and health. We also provide 2 clinical cases to illustrate the process of family acceptance of a transgender youth and a gender nonconforming youth who was neither a sexual minority nor transgender. Clinical implications of family acceptance and rejection of LGBT youth are discussed.